WINE TOURISM IN WESTERN MOLDOVA - TO A FUTURE ALSACE? - Mihaela MANEA (Management & Marketing)
Wine tourism has emerge as a form of redinamization, recovery of wine products. It was necessary such a tourism form for the wine-growing regions to assert in this tourist industry through landscapes as well as the products offered. Countries like France, Italy and Spain are already among the most definitive statement in this area, being basically those that outline the so-called Old World of the wine tourism domain. This is due to a long history of viticulture, terroir, winemaking method and cultural heritage. Romania is also on the wine countries list being part of the top ten countries according to the hierarchy made by OIV. Wine tourism started to come also in Romania, increasingly more wineries adopting wine recovery forms through tourism. It is adopting foreign models of wine tourism but keeping the local specific. Thus Moldova, the largest wine region began to adapt some wine tourism development models and this article will demonstrate whether this model is beneficial for Moldova.